THE INFLUENCE OF FACTORS ON THE COMPETITIVENESS OF THE MARKET OF TOURIST SERVICES IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The deep crisis due to the spread of the COVID-19 pandemic has become the most tangible for the tourism industry worldwide. The closure of borders in most countries has affected the review of opportunities for domestic tourism. Therefore, this period should be used for deep scientific research of the reasons for the low level of competitiveness of Ukrainian tourism and to develop directions, strategies and tactics to improve the competitive status of Ukrainian tourism in the world.The aim of the study is to analyze the favorable and critical indicators of competitiveness assessment in tourism in Ukraine and to determine the factors influencing the development of tourist destinations through the promotion of active eco-tourism. The task of the article is to offer practical directions for improving the industry at the institutional and local level in order to increase the competitiveness of destinations and their development through the creation of products of active ecological tourism.The importance of ecological tourism for the development of the industry and rural areas is substantiated. The influence of factors on the competitiveness of the industry is analyzed through the indicators of the Tourism and Travel Competitiveness Index, which allowed to identify the most significant of them that need the attention of managers at the macro, meso and micro levels. An assessment of tourist flows in Ukraine, which is the basis for justifying decisions, in search of reasons for the low level of tourist attractiveness of certain types of tourism.A group of factors at the institutional level is singled out and directions for improving state policy to support the industry and development of individual tourist destinations are proposed, namely: the need to review the activities of rural estates and the role of self-regulatory organizations in quality control of provided services; creation of economic incentives for domestic and inbound tourism operators; creation of a trust fund for the use of tourist tax; application of sanctions to business entities that violate the conditions of activity; introduction of modern information and communication technologies at the national and regional levels; development and implementation of an effective communication strategy; development of state targeted programs to promote a healthy ecological lifestyle through incentives for active ecological tourism, which will ultimately contribute to the revival of the industry after the crisis.
Keywords: competitive environment, the market of tourist services, tourist company